A Clinical Study of 100 Cases of Eclampsia In Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2009)
Eclampsia is the occurrence of one or more convulsion in association with the syndrome of pre eclampsia. It is relatively uncommon in developed countries where it complicates about one in every 200 deliveries. Eclampsia can be 20 times more common in developing countries and it probably accounts for more than 50,000 maternal deaths worldwide each year. Which anticonvulsant for women with eclampsia Evidence from the collaborative Eclampsia Trial lancet 1995, 345, 1445-63. The main objective of this study was to observe the clinical profile of antepartum eclampsia cases. The study was carried out with 100 cases that were selected randomly during year 2004. 58% of the patients were primigravida; among them 25% patients were in age group 15-14 years. About 95% patients were illiterate, low socio economic group, and in 53% patients' convulsion occurred in 32-37 weeks of pregnancy.Among 100 patients, 71 patients had normal vaginal delivery and 25% patients needed Caesarean section. Maternal mortality rate was 2%, perinatal mortality was 38%. Perinatal mortality was higher in vaginal group (12%) than LSCS group (7%). doi: 10.3329/taj.v17i2.3450 TAJ 2004; 17(2): 80-83